Agonistic Interactions in Raptors of the Pampas Region - Baladron Felix, Alejandro Victor (2013)
In this study, we evaluated the interspecific agonistic responses of raptors and nonraptors, elicited by the presence of five raptor species (Circus cinereus, C. buffoni, Rupornis magnirostris, Elanus leucurus, and Geranoaetus melanoleucus) in the Pampas region of Argentina. We registered 62 agonistic interaction events, most of them involving two raptor species (58%). During these events we registered 122 attacks, 10 persecutions, and three cases of kleptoparasitism. Milvago chimango was the most important aggressor species among raptors, and Vanellus chilensis among non-raptor birds. Attacks in groups were more frequently performed by non-raptors (61.5% of the events involved two or more aggressor individuals) than by raptors (68.5% of the events involved only one aggressor). This study represents a primary approach to one scarcely explored aspect of raptor behavior in southern South America